Innovative Methods for the Integration of Immunosensors Based on Magnetic Nanoparticles in Lab-on-Chip. (2017) - Lefebvre, Olivier; Nkot, Fabrice Mbock; Smadja, Claire; Martincic, Emile; Woytasik, Marion; Ammar, Mehdi
Abstract: Commonly immunoassay using magnetic nanoparticles (MNP) are performed under the control of permanent magnet close to the micro-tube of reaction 1 . Using a magnet gives a powerful method for driving MNP but remains unreliable or insufficient, for a fully integrated immunoassay on lab-on-chip. The aim of this study is to develop a novel lab-on-chip (Figure 1.B) for high efficient immunoassays to detect pathogenic bacteria with microcoils employed for trapping MNP during the biofunctionalization steps. Studies on bacteria are mainly based on E. Coly 2, 3 which is a non-pathogenic bacteria and can be find everywhere. In our case we use ovalbumin which is defined as a biodefense model protein. The objectives are essentially to optimize their efficiency for biological recognition, by assuring a better bioactivity (antibodies-ovalbumin), and detect small concentrations of the targeted protein (∼10 pg/mL). The fluidic microsystem is made of PDMS, which is micro-molded in SU8, it had channels with 50 μm height and 500 μm width. Microfluidic conditions permit a faster biofonctionnalisation step than in test tube and allow capture and detection of biological elements integrated in lab-on-chip. Microcoils are electrodeposited on silicon using cupper. They are microfabricated with cupper wire of 10 μm height, 10 μm width, 10 μm space between wire and 45 spires. Microcoils are encapsulated in microfluidic chip by covering them with a spin-coated thin layers of PDMS. Microcoils give a local and efficient trapping of MNP and a fully integrated device. Biological activity is studied respecting ELISA protocol with ovalbumin as protein of interest. To graft the primary antibody and protect the free area of MNP we used carboxylic as terminal group for grafting antibodies and BSA (Bovine Serum Albumin) for passivation (Figure 1.A). We characterize this method by measuring the intensity of the antibody of detection using FITC (Fluorescein isothiocynathe). Intensity is detected by fluorescent microscope connected to the microfluidic plateform and images are processed using a home-made script. First we studied the response of immunoassays complex function of MNP size (200 nm, 300 nm and 500 nm), we confirmed that with a lower diameter we increase the intensity detected, following specific surface formula (1), (2), (3). Regarding the magnetic force needed (depending of several parameters including magnetic field and parameters of the particle) and the intensity detected we selected 300 nm size of NPM. We studied the response of immunoassays complex function of ovalbumin concentration. We realized different immunoassays by controlling MNP (Figure 1.C&D) in test tube and in microfluidic device using a magnet. The comparison between these two experiments allow us to show an improved limit of detection ( L.O.D. = I 0 – 3 × σ D ; σ D : standard deviation, I 0 : Blank Intensity) using microfluidic conditions and controlling MNP trapping with a magnet. In conclusion, we developed an original and innovative fully-integrated immunoassay on lab-on-chip in order to detect bacteria. We use ovalbumin as a Biodefense model protein, magnetic nanoparticles and ELISA protocol to perform immunoassay. We demonstrate the advantage of microfluidic chip with a optimize limit of detection (less four time). Adding microcoils, we hope obtain a fully integrated lab-on-chip which should allow us to attain optimalspecificity and sensitivity for the detection of very low bacteria concentration for biodefense applications. We developed an original and innovative fully-integrated immunoassays on LOC which will open the route to a very high sensitive and specific immunoassay platform.